Revisiting the role of cyanobacteria-derived metabolites as antimicrobial agent: A 21st century perspective - Kar, Joyeeta; Ramrao, Devde Pandurang; Zomuansangi, Ruth; Lalbiaktluangi, C.; Singh, Shiv Mohan; Joshi, Naveen Chandra; Kumar, Ajay; Kaushalendra,; Mehta, Suryakant; Yadav, Mukesh Kumar; Singh, Prashant Kumar (Frontiers in Microbiology, 2022)
Cyanobacterial species are ancient photodiazotrophs prevalent in freshwater bodies and a natural reservoir of many metabolites (low to high molecular weight) such as non-ribosomal peptides, polyketides, ribosomal peptides, alkaloids, cyanotoxins, and isoprenoids with a well-established bioactivity potential. These metabolites enable cyanobacterial survival in extreme environments such as high salinity, heavy metals, cold, UV-B, etc. Recently, these metabolites are gaining the attention of researchers across the globe because of their tremendous applications as antimicrobial agents. Many reports claim the antimicrobial nature of these metabolites; unfortunately, the mode of action of such metabolites is not well understood and/or known limited. Henceforth, this review focuses on the properties and potential application, critically highlighting these metabolites' possible mechanisms of action to offer further translational research. The review also aims to provide a comprehensive insight into current gaps in research on cyanobacterial biology as antimicrobials and hopes to shed light on the importance of continuing research on cyanobacteria metabolites in the search for novel antimicrobials.